Penguatan Nilai-Nilai Spiritual Dalam Pendidikan Dasar di SDN 1 Bojong Kulon - Nurkholis; Navysa Maulina Rahmawati; Sheli Apriliyana (PT. Hasba Edukasi Mandiri, 2025)
This study aims to identify and analyze the implementation of the spiritual values strengthening program at the elementary education level at SDN 1 Bojong Kulon. Through a descriptive qualitative approach, this study explores the strategies, challenges, and impacts of various spiritual programs integrated into the curriculum and extracurricular activities. Data collection was carried out through participatory observation, in-depth interviews with 27 informants consisting of class teachers, religious education teachers, and students, and analysis of school documents during the period January to June 2024. The research was conducted in March 2024. This research reveals that SDN 1 Bojong Kulon enhances spiritual values by applying four principal strategies, namely: (1) integration of spiritual values in thematic learning, (2) daily habituation programs, (3) spiritual-based extracurricular activities, and (4) school-family partnerships. The main challenges faced include limited teacher training, diversity of students' family backgrounds, and the influence of digital media. Nevertheless, the implementation of the spiritual values strengthening program has shown a positive impact on student behavior, as observed through improved discipline practices, increased honesty in daily interactions, enhanced tolerance toward differences, and greater empathy in peer relationships. This study concludes that a holistic and collaborative approach between schools and families is the key to the success of a program to strengthen spiritual values at the elementary education level.